Vector Analysis of the Effects of FS-LASIK and Toric ICL for Moderate to High Astigmatism Correction - Kaijian Chen; Zongli Hu; Jihan Zhou; Ting Yu; Jie Xu; Ji Bai; Jian Ye (Journal of Ophthalmology)
Purpose. To estimate the treatment effectiveness of femtosecond-assisted laser in situ keratomileusis (FS-LASIK) and Toric implantable collamer lens (Toric ICL) for moderate and high astigmatism via vector analysis. Materials and Methods. The study involved 44 eyes from 44 patients who had a preoperative refractive cylinder ≥1.0 diopters (D) and underwent bilateral FS-LASIK or Toric ICL surgery. The examinations included corrected distance visual acuity measurement and subjective refraction before and 3 months after surgery. The astigmatic changes were estimated using vector analysis. Results. No statistically significant differences were found in cylindrical refraction and percentage of spherical equivalent within 0 D, ±0.50 D, ±1.00 D, and ±1.50 D between the FS-LASIK and Toric ICL groups at 3 months after surgery. The parameters of the vector analysis included intended refractive correction, surgically induced refractive correction, error vector, correction ratio, error ratio, error of magnitude, and error of angle, with no significant differences between the groups. However, error ratio the of the off-axis correction in the FS-LASIK and Toric ICL groups was 4.11 ± 3.02 and 8.11 ± 3.82, respectively, and the difference was significant (t = −2.46, p=0.02). Conclusion. Both FS-LASIK and Toric ICL were effective for correcting moderate and high astigmatism, although Toric ICL might produce a larger error of angle than FS-LASIK when an off-axis correction occurs.